1998
DOI: 10.1515/cclm.1998.055
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Reference Intervals for 34 Biochemical Analytes in Urban School Children and Adolescents

Abstract: Concentrations of 34 biochemical constituents of sera were determined on 998 randomly selected urban school children and adolescents aged 8-18 years from Zagreb, Croatia. Reference intervals were obtained by using non-parametric methods to estimate 2.5 and 97.5 percentiles of distribution as upper and lower normal reference intervals, according to the IFCC recommendations. These were compared to reference intervals in the healthy adult population, aged 20-30 years from the same geographical area. Serum glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
(15 reference statements)
7
27
2
Order By: Relevance
“…Women had a mean weight of 71.5 kg (ss8.9 kg) and a mean height of 1.64 m (ss0.05 m) and men had a mean weight of 86.1 kg (ss10.6 kg) and a mean height of 1.87 m (ss0.05 m). Results of standard laboratory tests for all subjects were within previously established reference intervals for the Croatian population (4,5,7). This study was performed with permission from the Ethical Committee of Medical School University of Zagreb, Croatia, and written consent was obtained from all participants.…”
Section: Reference Individuals and Samplessupporting
confidence: 68%
“…Women had a mean weight of 71.5 kg (ss8.9 kg) and a mean height of 1.64 m (ss0.05 m) and men had a mean weight of 86.1 kg (ss10.6 kg) and a mean height of 1.87 m (ss0.05 m). Results of standard laboratory tests for all subjects were within previously established reference intervals for the Croatian population (4,5,7). This study was performed with permission from the Ethical Committee of Medical School University of Zagreb, Croatia, and written consent was obtained from all participants.…”
Section: Reference Individuals and Samplessupporting
confidence: 68%
“…Increase in creatinine with the advancement of age for both sexes could be due to muscle degradation with age. Higher creatinine levels in males than in females may be due to the greater muscle mass in males than females [14]. The higher UA in males relative to females could be explained by the higher clearance rate in females than in males [15].…”
Section: Results Are Expressed As Means (X) ± Standard Deviation (Sd)mentioning
confidence: 99%
“…Other authors have found a di¡erence between male and female values after puberty for both these enzymes, as is found in adults. 21,22 Our lack of discrimination may be due to a relatively small sample size for these age groups. Transformed results gave acceptable intervals in these cases even with the remaining data, which were still skewed.…”
Section: ^22mentioning
confidence: 94%